Strategi Bauran Pemasaran dan Rantai Pasok dalam Meningkatkan Usaha Penjualan Bakpia Basah Ahmad’s Family - Sholihah, Alfari Hatus; Habib, Muhammad Alhada Fuadilah (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The marketing mix is a device consisting of product, price, promotion and distribution, which will determine the level of marketing success and all of it is aimed at getting the desired response from the target market. The supply chain is a series of relationships or company activities that carry out the distribution of supplies of goods or services from the place of origin to the place of buyers or customers. Therefore, in running and developing a business, a marketing mix strategy and supply chain strategy are needed. The purpose of this study is to determine the 7P marketing mix strategy in increasing sales of Bakpia Ahmad's Family and the supply chain strategy to maintain the supply of raw materials in the production process so as to meet consumer demand. This research uses descriptive qualitative research methods and uses data collection techniques in the form of interviews, observation and documentation. The results showed that by implementing the 7P marketing mix strategy was able to increase bakpia sales. The 7P marketing mix strategy includes improving the quality of bakpia products, providing affordable prices, having a clean production site, a comfortable and clean shop, promoting through social media and word of mouth, friendly service, and using attractive product packaging. The results of the study further found that by implementing a supply chain strategy, the owner can fulfil the supply of raw materials, have a good working relationship with suppliers, provide a place to store raw materials, a production process that is tailored to the recipe, provide a place to store finished products, and provide distribution services that are ready to deliver.